Performance improvement of perovskite solar cells by employing a CdSe quantum dot/PCBM composite as an electron transport layer - Zeng, Xiaofeng; Zhou, Tingwei; Leng, Chongqian; Zang, Zhigang; Wang, Ming; Hu, Wei; Tang, Xiaosheng; Lu, Shirong; Fang, Liang; Zhou, Miao (Journal of materials chemistry. A, Materials for energy and sustainability, 2017)
Organic–inorganic hybrid perovskites have recently attracted considerable interest for application in solar cells due to their low cost, high absorption coefficient and high power conversion efficiency (PCE). Herein, we utilize a CdSe quantum dot/PCBM composite as an electron transport layer (ETL) to investigate the structure, stability and PCE of CH 3 NH 3 PbI 3−x Cl x perovskite solar cells. It is found that adsorption of the CdSe/PCBM composite reduces the roughness of the perovskite, leading to a high-quality film with a compact morphology. Density functional theory (DFT) based first-principles calculations show that CdSe enhances the chemical stability of CH 3 NH 3 PbI 3−x Cl x involving strong atomic orbital hybridization. Interestingly, an inorganic-terminated perovskite surface has much stronger interaction with CdSe compared to the surface with organic CH 3 NH 3 termination, with noticeable interfacial charge redistribution. Experiments on solar cells incorporating the CdSe/PCBM composite as the ETL show enhanced photocurrent and fill factor, which is related to the in-built electric field between CH 3 NH 3 PbI 3−x Cl x and CdSe that greatly facilitates the separation of electron and hole pairs. We show an improved PCE of 13.7% with enhanced device stability in a highly humid atmosphere. These joint theoretical–experimental results may provide a new aspect for improving the structural stability and operating performance of optoelectronic devices based on perovskite structures.